On relative widths of classes of differentiable functions. II - Subbotin, Yu. N.; Telyakovskii, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain an upper bound for the least value of the factor М for which the Kolmogorov widths d_n (W_C^r, C) are equal to the relative widths K_n (W^C_r, MW^C_j, C) of the class of functions W_C^r with respect to the class MW^C_j, provided that j > r. This estimate is also true in the case where the space L is considered instead of C.